Control of inorganic and organic phosphorus molecules on microbial activity, and the stoichiometry of nutrient cycling in soils in an arid, agricultural ecosystem - Pamela Chavez-Ortiz; John Larsen; Gabriela Olmedo-Alvarez; Felipe García-Oliva (PeerJ)
Background The dynamics of carbon (C), nitrogen (N), and phosphorus (P) in soils determine their fertility and crop growth in agroecosystems. These dynamics depend on microbial metabolism, which in turn depends on nutrient availability. Farmers typically apply either mineral or organic fertilizers to increase the availability of nutrients in soils. Phosphorus, which usually limits plant growth, is one of the most applied nutrients. Our knowledge is limited regarding how different forms of P impact the ability of microbes in soils to produce the enzymes required to release nutrients, such as C, N and P from different substrates. Methods In this study, we used the arable layer of a calcareous soil obtained from an alfalfa cropland in Cuatro Cienegas, México, to perform an incubation experiment, where five different phosphate molecules were added as treatments substrates: three organic molecules (RNA, adenine monophosphate (AMP) and phytate) and two inorganic molecules (calcium phosphate and ammonium phosphate). Controls did not receive added phosphorus. We measured nutrient dynamics and soil microbial activity after 19 days of incubation. Results Different P molecules affected potential microbial C mineralization (CO2-C) and enzyme activities, specifically in the organic treatments. P remained immobilized in the microbial biomass (Pmic) regardless of the source of P, suggesting that soil microorganisms were limited by phosphorus. Higher mineralization rates in soil amended with organic P compounds depleted dissolved organic carbon and increased nitrification. The C:N:P stoichiometry of the microbial biomass implied a change in the microbial community which affected the carbon use efficiency (CUE), threshold elemental ratio (TER), and homeostasis. Conclusion Different organic and inorganic sources of P affect soil microbial community structure and metabolism. This modifies the dynamics of soil C, N and P. These results highlight the importance of considering the composition of organic matter and phosphate compounds used in agriculture since their impact on the microbial activity of the soil can also affect plant productivity.